Expression Profiling Coupled with In-silico Mapping Identifies Candidate Genes for Reducing Aflatoxin Accumulation in Maize - Dhakal, Ramesh; Chai, Chenglin; Karan, Ratna; Windham, Gary L.; Williams, William P.; Subudhi, Prasanta K. (Frontiers in Plant Science, 2017)
Aflatoxin, produced by Aspergillus flavus, is hazardous to health of humans and livestock. The lack of information about large effect QTL for resistance to aflatoxin accumulation is a major obstacle to employ marker-assisted selection for maize improvement. The understanding of resistance mechanisms of the host plant and the associated genes is necessary for improving resistance to A. flavus infection. A suppression subtraction hybridization (SSH) cDNA library was made using the developing kernels of Mp715 (resistant inbred) and B73 (susceptible inbred) and 480 randomly selected cDNA clones were sequenced to identify differentially expressed genes (DEGs) in response to A. flavus infection and map these clones onto the corn genome by in-silico mapping. A total of 267 unigenes were identified and majority of genes were related to metabolism, stress response, and disease resistance. Based on the reverse northern hybridization experiment, 26 DEGs were selected for semi-quantitative RT-PCR analysis in seven inbreds with variable resistance to aflatoxin accumulation at two time points after A. flavus inoculation. Most of these genes were highly expressed in resistant inbreds. Quantitative RT-PCR analysis validated upregulation of PR-4, DEAD-box RNA helicase, and leucine rich repeat family protein in resistant inbreds. Fifty-six unigenes, which were placed on linkage map through in-silico mapping, overlapped the QTL regions for resistance to aflatoxin accumulation identified in a mapping population derived from the cross between B73 and Mp715. Since majority of these mapped genes were related to disease resistance, stress response, and metabolism, these should be ideal candidates to investigate host pathogen interaction and to reduce aflatoxin accumulation in maize.